2014
DOI: 10.1002/jso.23643
|View full text |Cite
|
Sign up to set email alerts
|

Carinal resection and reconstruction in thoracic malignancies

Abstract: Malignant tumors involving the carina can be controlled with carinal surgery with acceptable mortality and morbidity. Patients with thoracic malignancy involving the carina should be considered as surgical candidate based on disease extent and functional status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 20 publications
4
29
0
1
Order By: Relevance
“…Neoplasms involving the carina and/or distal trachea without systemic or lymphatic metastases are uncommon but not rare (1,2). Most of these patients were diagnosed at an advanced stage, and were likely to be no longer candidates for surgical resection (1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neoplasms involving the carina and/or distal trachea without systemic or lymphatic metastases are uncommon but not rare (1,2). Most of these patients were diagnosed at an advanced stage, and were likely to be no longer candidates for surgical resection (1).…”
Section: Introductionmentioning
confidence: 99%
“…Most of these patients were diagnosed at an advanced stage, and were likely to be no longer candidates for surgical resection (1). On the other hand, patients with limited involvement of the carina or distal trachea can still be considered for extended surgical resection with airway reconstruction (1).…”
Section: Introductionmentioning
confidence: 99%
“…In this case, expandable metallic stent (EMS) was used, granulation tissue developed during follow-up and the patient died at 24 months. Among the 30 cases presented by Shin et al (2), three cases developed stenosis and stent was implemented in two. However, stent type and duration was not reported in the aforementioned study.…”
Section: Discussionmentioning
confidence: 98%
“…In these cases, surgical excision of the tumor has acceptable mortality and morbidity rates and has been shown to improve survival in carefully selected patients (6). Resectable primary non-www.respircase.com small cell tumors of distal trachea and tracheal carina are rare which require experienced surgeon and anesthesiologist (2). In a case series published by Shin et al (6), younger patients with improved physical conditions were found to be more suitable for surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Despite of central airway surgery being usually more complex and time-consuming procedures, the additional cross-field ventilation is a successful option in different central tracheoand carinoplasties, and is therefore used in the vast majority (12,13). One of the disadvantages of this technique is, that the cross-field tube can sometimes obstruct the view of the reconstruction site, thus periodical retraction of the tube may sometimes be necessary when performing airway anastomosis in order to improve exposure (3).…”
Section: Perioperative Ventilation During Surgery Of the Central Airwaysmentioning
confidence: 99%